Urethral Coitus in a Case of Vaginal Agenesis - Is Only Vaginoplasty Enough to Treat the Urinary Problems? - Mustafa Gazi Uçar; Tolgay Tuyan Ilhan; Ayse Gül Kebapçilar; Zekeriya Tosun; Çetin Çelik (Journal of Clinical and Diagnostic Research, 2016)
Urethral coitus is an extremely rare condition. Megalourethra and urinary incontinence due to urethral coitus in vaginal agenesis are unusual manifestations because these patients usually present with primary amenorrhea before becoming sexually active and receive treatment. A 24-year-old woman came to our clinic because of primary amenorrhea, sexual dysfunction, dyspareunia, megalourethra and urinary incontinence five months after her marriage due to urethral coitus. Based on these clinical and radiological findings a diagnosis of Mayer-Rokitansky-Kuster-Hauser Syndrome was made and patient underwent modified McIndoe Vaginoplasty. The elasticity of female urethra permits repeated coitus, together with the physical damage can probably lead to incontinence. In this case, after eliminating the underlying cause of disease with vaginoplasty, no other treatment was required. The integrity of sphincteric function and structural support of urethra might be regained without subjecting the patient to aggressive reconstructive surgical procedures.